2020
DOI: 10.1029/2019gl086867
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Rains Controlling Deposition of Saharan Dust Across the North Atlantic Ocean

Abstract: Mineral dust plays an important role in the atmospheric radiation budget as well as in the ocean carbon cycle through fertilization and by ballasting of settling organic matter. However, observational records of open‐ocean dust deposition are sparse. Here, we present the spatial and temporal evolution of Saharan dust deposition over 2 years from marine sediment traps across the North Atlantic, directly below the core of the Saharan dust plume, with highest dust fluxes observed in summer. We combined the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…The method assumes that the ITCZ represents a significant barrier to atmospheric dust transport and leads to an additional removal flux of dust (due to the strong precipitation). This assumption is supported by the strong latitudinal gradients in surface ocean dissolved Al and Fe concentrations across the ITCZ (Moore et al, 2009; Schlosser et al, 2014), as well as by modeled and observed associations between precipitation and dust deposition (van der Does et al, 2020;Yu et al, 2019). This wet deposition in the ITCZ results in a steeper gradient of dust deposition (with latitude) at the southern edge of the dust plume than is seen further north, in contrast to the approximately symmetrical pattern of aerosol thickness indicated by satellite retrievals (Yu et al, 2019).…”
Section: Latitudinal Trends Of 232 Th Flux and The Position Of The Itczmentioning
confidence: 91%
“…The method assumes that the ITCZ represents a significant barrier to atmospheric dust transport and leads to an additional removal flux of dust (due to the strong precipitation). This assumption is supported by the strong latitudinal gradients in surface ocean dissolved Al and Fe concentrations across the ITCZ (Moore et al, 2009; Schlosser et al, 2014), as well as by modeled and observed associations between precipitation and dust deposition (van der Does et al, 2020;Yu et al, 2019). This wet deposition in the ITCZ results in a steeper gradient of dust deposition (with latitude) at the southern edge of the dust plume than is seen further north, in contrast to the approximately symmetrical pattern of aerosol thickness indicated by satellite retrievals (Yu et al, 2019).…”
Section: Latitudinal Trends Of 232 Th Flux and The Position Of The Itczmentioning
confidence: 91%
“…The aspect ratio is computed by dividing the L by the width (W ) at the longest point that is perpendicular to L (Huang et al, 2020). The aerodynamic diameter (d a ) is calculated from the projected area diameter and the assumption that the particle is a sphere through the use of a volumetric shape factor, aerodynamic shape factor, and particle density from tables for specified oxides based on the chemical composition (Wagner and Leith, 2001;Ott et al, 2008).…”
Section: Scanning Electron Microscopy Imagingmentioning
confidence: 99%
“…A comparison of dust deposition fluxes in the sediment traps combined with precipitation data from satellites and with model simulations of dust deposition revealed that the main mechanism of dust deposition over the Atlantic Ocean is wet deposition, mostly occurring in summer (Bory et al., 2002; Van der Does et al., 2020). Over the eastern Atlantic, close to the source, dry deposition still plays a significant role, but along the downwind transect, wet deposition progressively becomes nearly the sole depositional process (Van der Does et al., 2020), as schematically illustrated in Figure 7. As it appears, precipitation events starting in summer (Figure 6) wash out large amounts of dust from the atmosphere (H. Yu et al., 2019), which are not sampled by the buoys as sampling is halted as soon as rain is detected by their weather sensors.…”
Section: Discussionmentioning
confidence: 99%
“…Sediment‐trap sample preparation is described in more detail by Van der Does et al. (2016, 2020). In brief, a biocide was added to the sampling bottles (HgCl 2 , 1.3 g L −1 ) and a pH buffer (borax; Na 2 B 4 O 7 · 10H 2 O, 1.3 g L −1 , pH ≈ 8) that created a density slightly higher than the ambient seawater to prevent the solution diffusing out of the bottles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation